Comparison of Copras, Vikor, and Waspas Methods in School Promotion Media Selection - Fatah Ridho Perdana; Gian Athallah; Perani Rosyani (International Journal of Integrative Sciences, 2023)
This Research Aims To Compare The COPRAS, VIKOR, And WASPAS Methods In A Decision Support System For Selecting School Promotion Media. Promotion Is An Important Activity To Improve The Impression And Competitiveness Of Schools. The Selection Of The Right Promotional Media Can Increase The Effectiveness Of The Promotion. The Three Methods Of COPRAS, VIKOR, And WASPAS Are Multicriteria Decision-Making Methods That Can Be Applied To Optimization Cases Such As The Selection Of Promotional Media. The Research Was Conducted By Applying The Three Methods To The Case Of Selecting Promotional Media For SMK Airlangga Using 5 Criteria: Cost, Time, Reach, Completeness, And Flexibility. The Results Show That The COPRAS And WASPAS Methods Produce The Same Ranking Of Alternatives With Billboards As The Best Alternative, While The VIKOR Method Is Different With Brochures As The Best Alternative. It Is Concluded That The WASPAS Method Is The Most Appropriate Because It Has Advantages In Terms Of Ease, Interpretation, And Consideration Of Criteria Weights